Penggunaan Sistem Basis Data Pada Portal Akademik Universitas Islam Negeri Sumatra Utara Medan - Sinarta Sigalingging; Tengku Aiena Zhafira; Raisa Azmi; Dinda Amelia; Nurbaiti Nurbaiti (Universitas 45 Surabaya, 2023)
This study aims to examine the use of the database system on the Academic portal of the State Islamic University of North Sumatra (UINSU). The UINSU Academic Portal functions as a means of information for UINSU students and academic activities. To increase the efficiency and effectiveness of information management, UINSU uses a database in its portal. The database system is used to store academic and administrative information such as student academic information, schedules, teacher information and other administrative information. This study used the case study method by taking a sample of UINSU Academic portal users. The data were obtained from interviews with UINSU Academic portal users and observations of the database system on the portal. The results of the study show that UINSU portal users benefit from having a database system. With a database system, users can easily and quickly access scientific and administrative information. In addition, the database system also helps information management to be more efficient and accurate.